Education and the age profile of literacy into adulthood - Cascio, Elizabeth U.; Clark, Damon; Gordon, Nora (NBER working paper series, 2008)
"It is widely documented that U.S. students score below their OECD counterparts on international achievement tests, but it is less commonly known that ultimately, U.S. native adults catch up. In this paper, we explore institutional explanations for differences in the evolution of literacy over young adulthood across wealthy OECD countries. We use an international cross-section of micro data from the International Adult Literacy Survey (IALS); these data show that cross-country differences in the age profile of literacy skills are not due to differences in individual family background, and that relatively high rates of university graduation appears to explain a good part of the U.S. "catch up." The cross-sectional design of the IALS prevents us from controlling for cohort effects, but we use a variety of other data sources to show that cohort effects are likely small in comparison to the differences by age revealed in the IALS. We go on to discuss how particular institutional features of secondary and postsecondary education correlate, at the country level, with higher rates of university completion"--National Bureau of Economic Research web site